Polish Decadence: Leopold Staff's Igrzysko in the European Context - Julia Przybos (Nordlit: Tidsskrift i litteratur og kultur, 2012)
Decadent authors writing about the past share a common artistic practice: revisionist creativity. I argue in my Zoom sur les décadents that this particular type of creativity uses as its main device recombination of legends, myths, and historical events. Historical, cultural or religious figures are reexamined and shown in a new unexpected light. I show in my book how Villiers de Isle-Adam conflates two crucial battles of the Ancient world: Marathon (490 BC) and Thermopiles (480 BC) in a short story called "Impatience de la foule." The final result of Villiers's telescoping of separate historical events is a seamless narrative. In Hugues Rebell's "Une Saison à Baia," Saint Paul attempts to convert Roman patricians who mock his incoherent speeches. In "La Gloire de Judas," Bernard Lazare departs from the Gospels and tells the tragic story of Judas whose betrayal made the salvation of the human race possible. In Lazare's short story, Judas is a self-effacing figure who doesn't act on his own but on Jesus Christ's specific order, who sworns him into secrecy.